THE DEVELOPMENT OF STUDENT WORKSHEETS TO GROW LEARNING MOTIVATION IN ADVANCED CALCULUS SUBJECTS - Taqwa, Muhammad (EMTEKA: Jurnal Pendidikan Matematika, 2026)
Post of the COVID-19 pandemic, online learning and self-directed learning have become commonplace, including advanced mathematics courses. Learning requires students to have a strong motivation to participate in their studies. The development of Student Worksheets (SW) is a strategy that can augment student motivation. The aim of this study was to provide a valid, practical, and effective technique for improving student motivation. This research was developmental, focusing on Student Worksheets development using the Plomp paradigm, which includes: (1) initial investigation, (2) design, (3) realization/construction, (4) testing, evaluation, and revision, and (5) implementation. The subjects of this study were 20 students registered in the Mathematics Education Program at STKIP Andi Matappa. Research instruments: (1) validation sheet for student worksheets (2) practicality sheets for student worksheets and (3) Student motivation questionnaire. The study's findings are as follows: (1) the content validity score of the SW is 0.82, classifying it as very high; (2) the practicality score of the SW is 690, signifying it fulfills very practical criteria; (3) in descriptive analysis, the average student motivation is 122.35 with a standard deviation of 18.48, categorizing it as adequate. In inferential analysis, the median student learning motivation for individuals undergoing SW therapy is classified as adequate, suggesting that the LKM treatment substantially improves student motivation. This signifies that the advanced calculus Student Worksheets developed is valid, effective, and successful in augmenting student motivation. Pasca Pandemi COVID-19, penggunaan pembelajaran daring dan belajar mandiri sudah lazim digunakan, termasuk mata kuliah matematika tingkat lanjut. Pembelajaran memerlukan motivasi yang kuat dari mahasiswa untuk berpartisipasi dalam studi mereka. Pengembangan Lembar Kerja Mahasiswa (LKM) merupakan strategi yang dapat meningkatkan motivasi mahasiswa. Tujuan penelitian ini adalah untuk menyediakan teknik yang valid, praktis, dan efektif dalam meningkatkan motivasi mahasiswa. Penelitian ini bersifat pengembangan, berfokus pada pengembangan perangkat lunak menggunakan paradigma Plomp, yang meliputi: (1) penyelidikan awal, (2) desain, (3) realisasi/konstruksi, (4) pengujian, evaluasi, dan revisi, serta (5) implementasi. Subjek penelitian ini adalah mahasiswa yang terdaftar dalam Program Pendidikan Matematika di STKIP Andi Matappa sebanyak 20 orang. Instrumen penelitian: (1) Lembar Validasi LKM; (2) Lembar Praktikalitas LKM; dan (3) Kuesioner motivasi mahasiswa. Temuan penelitian ini sebagai berikut: (1) skor validitas konten LKM adalah 0,82, dikategorikan sebagai sangat tinggi; (2) skor kepraktisan LKM adalah 690, menunjukkan bahwa LKM memenuhi kriteria sangat praktis; (3) Dalam analisis deskriptif, rata-rata motivasi mahasiswa adalah 122,35 dengan simpangan baku 18,48, yang dikategorikan sebagai memadai. Dalam analisis inferensial, median motivasi belajar mahasiswa yang telah diterapkan LKM diklasifikasikan kategori memadai, menunjukkan bahwa penerapan LKM secara signifikan meningkatkan motivasi mahasiswa. Hal ini menandakan bahwa LKM kalkulus lanjut yang dikembangkan valid, efektif, dan berhasil dalam meningkatkan motivasi mahasiswa.